Phenolic composition and antioxidant activity of industrial cork by-products - Santos, Sónia A O; Villaverde, Juan J; Sousa, Andreia F; Coelho, Jorge F J; Neto, Carlos P; Silvestre, Armando J D (Industrial Crops and Products, 2013)
Abstract The phenolic composition of cork powder and black condensate, two by-products from the cork industry, was investigated by the first time using high-performance liquid chromatography-multi-stage mass spectrometry (HPLC–MSn). The same methodology of extraction was applied to cork, for comparative purposes. Eighteen phenolic compounds were identified in cork, five of them are reported for the first time as its constituents. Sixteen and thirteen phenolic compounds were identified as cork powder and black condensate components, respectively, with only one compound of each residue published before as its constituent. The antioxidant activity of the extracts was evaluated, being, to our knowledge, the first study concerning the antioxidant activity of these cork residues. The extracts present an antioxidant activity higher than BHT, with black condensate showing the lowest IC50 value. These results, together with the phenolic content values, demonstrate the high potential of these residues as source of high value compounds.
Keywords: antioxidant activity; black condensate; Cork; cork powder; phenolic compounds; Quercus suber L.

Analysis of phenolic compounds in cork from Quercus suber L. by HPLC–DAD/ESI–MS - Fernandes, Ana; Sousa, André; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Food Chemistry, 2011)
The aim of the present work was to identify the extractable phenolic compounds present in cork from Quercus suber L. The structures of thirty three compounds were tentatively identiﬁed by liquid chromatography coupled to electrospray ionisation mass spectrometry (HPLC–DAD/ESI–MS). The majority of those compounds were gallic acid derivatives, in the form of either galloyl esters of glucose (gallotannins), combinations of galloyl and hexahydroxydiphenoyl esters of glucose (ellagitannins), dehydrated tergallic-C-glucosides or ellagic acid derivatives. Others were found to correspond to low molecular weight phenolic compounds, like acids and aldehydes. Mongolicain, a ﬂavanoellagitannin in which hydrolysable tannin and ﬂavan-3-ol moieties are connected through a carbon–carbon linkage, was also detected in cork from Q. suber L. The results illustrate the rich array of phenolic compounds present in cork.
Keywords: Cork; ellagitannins; Flavanoellagitannins; LC-DAD/ESI-MS; phenolic compounds; Quercus suber L.

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 19888728
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Wine Oxidation and the Role of Cork - Karbowiak, Thomas; Gougeon, Régis D; Alinc, Jean-Baptiste; Brachais, Laurent; Debeaufort, Frédéric; Voilley, Andrée; Chassagne, David (Critical Reviews in Food Science and Nutrition, 2009)
The present review aims to show the state of the art of oxidation mechanisms occurring especially in white wines by taking into account knowledge from different fields in relation to the subject. It is therefore divided into three main parts. First, the mechanisms of oxidation relevant to white wine are discussed in the light of recent scientific literature. Next, the phenomenon of oxygen solubility in wine during the winemaking process, and in particular during bottling is stated theoretically as well as practically. Finally, the aspect of wine conservation after bottling is examined with respect to mass transfers which may occur through the closure, with a special emphasis on cork. Currently, specific physico-chemical properties still make cork closures the most important closure type used for the wine market, and especially for high quality wines. This final section will also include a review of studies performed on this subject, which have been analyzed in detail from a theoretical mass transfer point of view, in order to assess the extent to which the proposed scientific tools and the observed tendencies are relevant to progress in the understanding of the impact of this parameter on the behavior of a wine.
doi: 10.1080/10408390802248585
Keywords: Cork; diffusion; Oxygen; permeability; phenolic compounds; solubility; white wine

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M L; Lamarti, A; Abdali, A; Badoc, A (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Low molecular weight phenols in cork stoppers - Pena-Neira, A; Hernández, T; GARCIA-VALLEJO, M C; Cadahía, E; de Simon, B F; Suarez, J A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1999)
In this work, we study the low molecular-weight polyphenols in cork stoppers obtained from commercial wine bottles and in samples taken at five stages of the cork stopper manufacturing process. The phenolic compounds (acids, aldehydes, and coumarins) were analyzed by high pressure liquid chromatography with photodiode array detector. The results were studied by statistical methods in order to determine the relationship among these compounds and their variability throughout the industrial processing. Discriminant analysis showed that the phenolic composition allows differentiation of each stage in the manufacture of cork stoppers and the different provenances of stoppers obtained from commercial wine bottles. The results showed wide variations in phenolic content among cork stoppers within each region and each winery.
Keywords: Cork; phenolic compounds; stopper manufacturing

Phenolic compounds in cork used for production of wine stoppers as affected by storage and boiling of cork slabs - Mazzoleni, V; Caldentey, P; Silva, A (AMERICAN JOURNAL OF ENOLOGY AND VITICULTURE, 1998)
Phenolic compounds (benzoic and cinnamic acid derivatives, vanillin, syringaldehyde and acetovanillone) were identified in cork used for production of wine stoppers by extraction in an ethanolic solution and by HPLC analysis. The effect of storage and boiling of cork slabs on these compounds were investigated. In each sample, cinnamic acids and vanillin have predominated among phenolics. Boiled cork was significantly different from raw slabs in the concentration of protocatechuic, caffeic, p-coumaric acids, and vanillin. The significant differences between cork from stored and from unstored slabs were evident in protocatechuic, 4-hydroxybenzoic, caffeic, and ferulic acids. Storage of slabs increased the amount of extractable cinnamic acids. On the other hand, boiling decreased the concentration of the same phenolic acids and increased that of vanillin. Boiling after storage can be beneficial to the cork quality, reducing the amount of potentially negative flavor compounds (cinnamic acids) and increasing potentially positive flavor compounds (vanillin).
Keywords: Cork; phenolic compounds; processing of cork slabs

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L. V.; Olivares-Bernabeu, C. (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L V; Olivares-Bernabeu, C (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Micropropagation of mature cork-oak (Querqus suber L.): establishment problems - Romano, A; Martins-Loução, M a (Scientia gerundensis, 1992)
Procedures have been developed to standardize the establishment stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds cultured in Gresshof and Doy (1972) (GD) medium were used as first explant. Establishment of cultures was very difficult due to browning of the tissue and/or the medium and bacterial contamination. Browning problems, probably due to phenolic compounds exudation of the primary explant, were found to be higher in winter. Nevertheless, initiation of cultures was possible all over the year, presumably due to the preconditioning of cuttings. Explants were established in a GD medium containing 6-benzlaminopurine (BAP) 1 mgl-1. Every 4 weeks the cultures were subcultured to the same GD medium and induced to proliferate being 4:1 the multiplication rate. Shoots were induced to elongate by decreasing BAP concentration. In vitro rooting on agar-solidified medium suplemented with 1 mgl-1 indolacetic acid (IAA) gave the best results. Liquid medium (sorbarod system) and in vivo rooting were also assayed.
Keywords: browning; contaminants; cork-oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture